From CSR Narratives to Accountable Practice in Philippine Education: Governance, Evidence, and Credible Reporting - Hazel S. Osano; Anik Yuesti; Joel Arante Alve (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
CSR in Philippine education was increasingly judged by what could be shown, not only what was claimed. A desk-based review of recent peer-reviewed studies and current reporting and quality guidance mapped how accountability expectations shifted toward clear criteria, consistent indicators, and traceable decisions. Evidence pointed to a common gap: reports often highlighted activities and beneficiaries but rarely tracked outcomes over time or explained how key decisions were made. Where accountability practice was stronger, roles were defined, a small set of material commitments was monitored, and limitations were stated plainly. Overly broad reporting expectations without matching capability produced compliance fatigue and encouraged symbolic disclosure. A right-sized approach emerged as the most workable path, linking CSR to quality routines and focusing measurement on equity, learner protection, staff welfare, and community outcomes.